Quantitative CT Densitometry for Predicting Intracerebral Hemorrhage Growth - Barras, C.D.; Tress, B.M.; Christensen, S.; Collins, M.; Desmond, P.M.; Skolnick, B.E.; Mayer, S.A.; Davis, S.M. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Intracerebral hemorrhage growth independently predicts disability and death. We hypothesized that noncontrast quantitative CT densitometry reflects active bleeding and improves predictive models of growth. MATERIALS AND METHODS: We analyzed 81 of the 96 available baseline CT scans obtained <3 hours post-ICH from the placebo arm of the phase IIb trial of recombinant factor VIIa. Fifteen scans could not be analyzed for technical reasons, but baseline characteristics were not statistically significantly different. Hounsfield unit histograms for each ICH were generated. Analyzed qCTD parameters included the following: mean, SD, coefficient of variation, skewness (distribution asymmetry), and kurtosis (“peakedness” versus “flatness”). These densitometry parameters were examined in statistical models accounting for baseline volume and time-to-scan. RESULTS: The coefficient of variation of the ICH attenuation was the most significant individual predictor of hematoma growth (adjusted R2 = 0.107, P = .002), superior to BV (adjusted R2 = 0.08, P = .006) or TTS (adjusted R2 = 0.03, P = .05). The most significant combined model incorporated coefficient of variation, BV, and TTS (adjusted R2 = 0.202, P = .009 for coefficient of variation) compared with BV and TTS alone (adjusted R2 = 0.115, P < .05). qCTD increased the number of growth predictions within ±1 mL of actual 24-hour growth by up to 47%. CONCLUSIONS: Heterogeneous ICH attenuation on hyperacute (<3 hours) CT imaging is predictive of subsequent hematoma expansion and may reflect an active bleeding process. Further studies are required to determine whether qCTD can be incorporated into standard imaging protocols for predicting ICH growth. BVbaseline ICH volumeICHintracerebral hemorrhageqCTDquantitative CT densitometryrFVIIarecombinant activated factor VIITTStime-to-scan (from ictus)